EFEKTIVITAS KOMUNIKASI MEDIA SOSIAL WHATSAPP SEBAGAI SARANA KOMUNIKASI PENYANDANG TUNARUNGU (Studi Pada Gerakan Untuk Kesejahteraan Tunarungu Indonesia (GERKATIN) Kota Pekanbaru) - Anggita Putri; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Whatsapp is one of the social media that has a lot of enthusiasts in Indonesia and rank second place of many social media platforms, Whatsapp is used from various groups of people in Indonesia, including deaf people. The theory used in this research is the theory of communication effectiveness as the main theory and new media theory as the supporting theory. The purpose of this study was to determine the effectiveness level of Whatsapp social media communication as a means of communication for deaf people.This study uses a quantitative research method, which data collection is carried out by distributing questionnaires directly to respondents and distributing them using a link via Google Form to members of GERKATIN Pekanbaru City. Who are determined through random sampling techniques to 154 respondents. The data analysis technique in this study used descriptive statistical techniques.The results of this study indicate that the level of effectiveness of Whatsapp social media communication as a means of communication for deaf people studying at GERKATIN Pekanbaru City is classified as very effective. It is seen from the data processing which is based on six indicators, each of which reached an average of 3.56 scale indicator Message Recipients (Receiver), a scale of 3.43 to indicators Your Message (Content), the scale of 3, 49 on indicators of media, magnitude 3.37 on the indicator format, scale of 3.31 on the indicator to indicator message source (Source),and a scale of 3.41 to indicators Timeliness (Timing). So that the conclusion obtained using the average formula of all indicators is 3.43 which is included in the very effective scale range. This shows that Whatsapp social media is a very effective medium as a means of communicating with deaf people. Keywords : Effectiveness Communication, Social Media, Deaf People